Modeling cognitive load in problem-based biology learning: Effects of material complexity and teaching strategy - Handi Darmawan; Netti Yuniarti; Stephani Yane; Tran Thi Huong Xuan; Ninda Permasari (Universitas Muhammadiyah Malang, 2026)
Background-Although PBL is effective in biology learning, this approach often triggers cognitive overload when the complexity of the material and instructional demands exceed students' working memory capacity, while there is currently no empirically validated causal model available to explain these interactions. Objectives-This study aims to examine the effects of material complexity and teaching strategies on students' cognitive load and to assess the interaction of the two in PBL-based biology learning. Method-A quantitative explanatory design was employed with 240 eighth-grade students from junior high schools in Pontianak, Indonesia. Data were collected using validated 5-point Likert scales and analyzed through Structural Equation Modeling (SEM) via AMOS 26.0, encompassing confirmatory factor analysis, goodness-of-fit evaluation, structural path analysis, and Sobel mediation test. Measurement quality was confirmed with AVE values ranging from 0.58 to 0.65 and CR values from 0.81 to 0.88. Results-Material complexity (β = 0.59; p < 0.001) and teaching strategies (β = 0.38; p < 0.001) significantly predicted cognitive load. A significant mediation effect was confirmed via Sobel test (z = 2.26; p < 0.05), indicating that teaching strategies partially mediate the relationship between material complexity and cognitive load formation. Conclusions-Adaptive instructional design grounded in Cognitive Load Theory encompassing scaffolding, content segmentation, and structured sequencing is essential to ensure PBL is both pedagogically effective and cognitively ergonomic.